PERIODISASI TOKOH ILMU NAHWU ALIRAN BASRAH - Dollah Sobari (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2014)
Abstract: Periodization figures of nahwu science (syntax) of Basrah current is divided into six periods, one period of the initiators and five periods of development. In each period, there are characters who are very instrumental with brilliant ideas. Abul-Aswad a'd-Duwalī is the originator of the birth of science nahwu figure. The characters that appear after Abul-Aswad a'd-Duwalī have some notions contradiction with previous figures opinion of their teacher. Dynamics like these that delivers the development of science nahwu (syntax) has classic peaked during the Sibawaihi. In addition, the difference of opinion in the next period triggered a new stream in science nahwu. Factors that encourage the development of science nahwu in Basrah is a factor of sociology, cultural, and strategic geographical location with many travelers from other regions, the stability of a society that is far from the wars and violence, the number of learning activities in the mosque of Basra and their Mirbad market as a place for expression in the work, especially the field of language and literature. Keywords: -periodization, -Nahwu (Syntax),-Basrah